Provision of dental services for vulnerable groups: a scoping review on children with special health care needs - Peivand Bastani; Mohammadtaghi Mohammadpour; Arash Ghanbarzadegan; Giampiero Rossi-Fedele; Marco A. Peres (BMC, 2021)
Abstract Background The provision of dental services for children with special health care needs (CSHCN) needs to be considered by policymakers. This study is aimed to explore the determinant factors affecting dental and oral services provision for this vulnerable group. Methods A review was conducted applying the 9-steps approach. Five scientific databases of PUBMED, SCOPUS, Web of Science and PROQUEST and EMBASE were searched up to 10.07.2021, applying appropriate keywords. Thematic analysis was used to analyse the extracted data, and a conceptual map was developed according to JBI manual for evidence synthesis. Results From the abstracts of the 136 articles that fulfilled the inclusion criteria, 56 articles were included. Five main themes were identified as determinants affecting the provision of dentistry services for CSHCN, including needs assessment, policy advice, oral health interventions, providers' perception and access barriers. According to the developed conceptual map, assessing the needs of CSHCN can lead to particular policy advice. Regarding the policies, appropriate oral health interventions can be presented. These interventions, along with providers' perception about service delivery to CSHCN and the barriers to access them, determine the provision of dentistry services for CSHCN. Conclusions An effective needs assessment of CSHCN and their parents/carers can lead to evidence-informed policymaking and applicable policy advice according to the needs. Then policymakers should develop interventions to improve the community's health literacy, as well as support the seeking behaviours for appropriate services. Policymakers should also consider how to limit the barriers to accessing oral and dental health by CSHCN to decrease disparities.